Pollen record of the centennial climate changes during 9–7 cal ka BP in the Changjiang (Yangtze) River Delta plain, China. Issue 2 (28th February 2017) - Song, Bing; Li, Zhen; Lu, Houyuan; Mao, Limi; Saito, Yoshiki; Yi, Sangheon; Lim, Jaesoo; Li, Zhen; Lu, Anqing; Sha, Longbing; Zhou, Rui; Zuo, Xinxin; et al.
Abstract: We reconstructed the centennial climate changes for the period of 9–7 cal ka BP in the upper region of the Changjiang (Yangtze) River Delta plain. A general warming and wetting trend from 8560 to 7220 cal yr BP was indicated by the decrease in Quercus (deciduous) and increases in Quercus (evergreen), Pinus, and Polypodiaceae spores. However, there were several brief climate fluctuations. A notable palynological change, from regional assemblages dominated by arboreal pollen to local assemblages mainly consisting of nonarboreal pollen, reflects climate fluctuations. The key indices of Quercus (deciduous), Pinus, herbs, fern spores, and palynological concentrations showed similar signs of centennial climate fluctuations. We suggest that the climate changes of the Dongge Cave and Yangtze River Delta regions were mainly affected by the East Asian summer monsoon (EASM) during the period of 9–7 cal ka BP. The general warming trend may be associated with an intensified EASM, and solar activity may be one of the important factors driving the centennial climate changes. The ~8.2 ka event was also recorded in the Yangtze River Delta region, which suggests that there was a close relationship between the EASM and Greenland climate during the early Holocene.